Fipronil Impairs Proliferation in the Olfactory Neurogenic Region and Alters Low Temperature Sensitivity in Adult Mice - Fabianová, Kamila; Pisko, Jozef; Fabian, Dušan; Martončíková, Marcela; Raček, Adam; Račeková, Enikő (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(4):293